2010
DOI: 10.4293/108680810x12785289144449
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-Assisted Management of Impalpable Testis in Patients Older than 10 Years

Abstract: Laparoscopic-assisted single-stage orchiopexy appears to be a safe, effective procedure for intraabdominal testis in adolescent and older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This fact was also seen in our study where age group ranged between 13-34 years with the mean age of 20.75 + 5.98. Similar result was also seen by Sangrasi et 11,12 . But another study revealed 63% left sided testes 13 .…”
Section: Discussionsupporting
confidence: 90%
“…This fact was also seen in our study where age group ranged between 13-34 years with the mean age of 20.75 + 5.98. Similar result was also seen by Sangrasi et 11,12 . But another study revealed 63% left sided testes 13 .…”
Section: Discussionsupporting
confidence: 90%
“…11 A similar mean age of 8.3±7.9 years was observed by David et al in boys with undescended testes in Nigeria 12 while Tseng et al reported it to be 9.2±1.2 years in Taiwan. 13 We observed that majority (77.9%) of the children had right while 15 15 Dar et al observed similar frequency of right and left undescended testes in Indian boys and reported it to be 79.0% and 21.0% respectively. 16 A comparable frequency of right (76.5%) and left (23.5%) undescended testes has been reported by Tseng et al in Taiwan.…”
Section: Discussionmentioning
confidence: 57%
“…Even in adolescent and adult patients, laparoscopic orchidopexy is a safe and successful procedure for nonpalpable intra-abdominal UDT. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Untreated cryptorchidism has deleterious effects on the testis over time, with the risk of malignancy in intra-abdominal testis as high as 5%, increasing with age. [ 9 10 11 12 ] Therefore, early investigations and treatment of impalpable testis are important to increase the likelihood of fertility and to allow early diagnosis of possible testicular malignancies.…”
Section: Introductionmentioning
confidence: 99%